Topical Approaches to Managing Socio-Economic Development of Territories - Anna A. Urasova (Ural State University of Economics, 2018)
The paper focuses on the main approaches to the management of socio-economic development of territories. The methodological basis of the work is the logical analysis of the existing theoretical approaches, as well as cause and effect analysis in terms of formulation of the core definitions. The authors presents an in-depth assessment of the application of the complex and integrated approaches to territorial management using the case studies of a number of regions of the Russian Federation. We also conclude that the efficiency of territorial development mirrors the level of involvement of economic and social resources in economic turnover, i.e. the degree of exploiting the socio-economic potential which is directly related to the choice of a particular approach to management of territories. That is why the optimal approach in combination with special features of a particular territory are capable of producing a significant managerial effect. The case of P erm kray’s territories aptly illustrate this condition.